Comprehensive Approach to Investigate the De‐/Lithiation Mechanism of Fe‐Doped SnO2 as Lithium‐Ion Anode Material. (1st June 2022) - Asenbauer, Jakob; Wirsching, Anna‐Lena; Lang, Marcel; Indris, Sylvio; Eisenmann, Tobias; Mullaliu, Angelo; Birrozzi, Adele; Hoefling, Alexander; Geiger, Dorin; Kaiser, Ute; Schuster, Rolf; Bresser, Dominic
Abstract: Iron‐doped tin oxide (Sn0.9 Fe0.1 O2 ), and specifically carbon‐coated Sn0.9 Fe0.1 O2 (Sn0.9 Fe0.1 O2 ‐C) provides high reversible capacity and a reasonably low de‐/lithiation potential owing to the combined conversion and alloying mechanism. The initial (quasi‐)amorphization during the first lithiation, however, renders an in‐depth understanding of the reaction mechanism challenging. Herein, a comprehensive investigation via a set of highly complementary characterization techniques is reported, including operando X‐ray diffraction, ex situ 119 Sn and 57 Fe Mössbauer spectroscopy, ex situ 7 Li NMR spectroscopy, operando isothermal microcalorimetry (IMC) of Li‖Sn0.9 Fe0.1 O2 ‐C coin cells, and electrochemical microcalorimetry of single Sn0.9 Fe0.1 O2 ‐C electrodes. The combination of these advanced techniques allows for detailed insights into the lithiation and delithiation mechanism and the potential determining processes, despite the (quasi‐) amorphous nature of the active material after the initial lithiation. Abstract : The investigation of the reaction mechanism of lithium‐ion electrode materials that turn (quasi‐)amorphous upon cycling, such as iron‐doped tin oxide, provides a particular challenge with regard to common characterization techniques. Complementing these commonly used techniques by operando calorimetry and ex situ Mössbauer and solid‐state 7 Li‐NMR spectroscopy enables a deeper understanding and, thus, offers the chance to further optimize such materials.